2016
DOI: 10.1109/tcbb.2015.2510002
|View full text |Cite
|
Sign up to set email alerts
|

MiRTDL: A Deep Learning Approach for miRNA Target Prediction

Abstract: MicroRNAs (miRNAs) regulate genes that are associated with various diseases. To better understand miRNAs, the miRNA regulatory mechanism needs to be investigated and the real targets identified. Here, we present miRTDL, a new miRNA target prediction algorithm based on convolutional neural network (CNN). The CNN automatically extracts essential information from the input data rather than completely relying on the input dataset generated artificially when the precise miRNA target mechanisms are poorly known. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Although performance may increase significantly by changing other parameters, for example, the batch size and the number of units in the remaining layers, our results support the importance of spatial features in miRNA target prediction. One previous study, the miRTDL study, applied CNN in miRNA target prediction, however, the authors only used CNN as a classifier (Cheng, et al, 2016). The miTAR model is the first to use CNN to capture the potential spatial features directly from the sequences of miRNAs and genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although performance may increase significantly by changing other parameters, for example, the batch size and the number of units in the remaining layers, our results support the importance of spatial features in miRNA target prediction. One previous study, the miRTDL study, applied CNN in miRNA target prediction, however, the authors only used CNN as a classifier (Cheng, et al, 2016). The miTAR model is the first to use CNN to capture the potential spatial features directly from the sequences of miRNAs and genes.…”
Section: Discussionmentioning
confidence: 99%
“…Beside DeepMirTar and miRAW, we compared our approach to two other published deep learning methods: deepTarget and miRTDL (Cheng, et al, 2016;Lee, et al, 2016). They were developed earlier, hence, the training datasets they used are much smaller.…”
Section: Performance Comparison With Earlier Studies Using Test Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of prediction tools are based on the assumption that it is the 12 miRNA seed region -generally defined as a 6 to 8 nucleotide sequence starting at the 13 first or second nucleotide -that contains almost all the important interactions between 14 a miRNA and its target and their focus is on these canonical sites. This seed-centric 15 view has been supported by structural studies [5] and a widely cited report [6] that 16 investigated the importance of other (non-canonical) regions within a miRNA and 17 concluded their contributions had relatively low relevance compared to the (canonical) 18 seed region. However, more recent studies have revealed that many relevant targets are 19 implemented via non-canonical binding and involve nucleotides outside the seed region, 20 indicating that the entire miRNA should be considered in target prediction 21 algorithms [3,7,8].…”
mentioning
confidence: 85%
“…They used the model to detect a unified representation of latent features, capture both intra- and cross- modality correlations, and to identify key genes that may play distinct roles in the pathogenesis between different cancer subtypes. Cheng et al [16] designed a miRNA prediction algorithm based on convolutional neural network (CNN). The CNN automatically extracts essential information from the input data while the exact miRNA target mechanisms are not well known.…”
Section: Introductionmentioning
confidence: 99%